2021
DOI: 10.1093/braincomms/fcab297
|View full text |Cite
|
Sign up to set email alerts
|

Persistent neuropsychiatric symptoms after COVID-19: a systematic review and meta-analysis

Abstract: The nature and extent of persistent neuropsychiatric symptoms after COVID-19 are not established. To help inform mental health service planning in the pandemic recovery phase, we systematically determined the prevalence of neuropsychiatric symptoms in survivors of COVID-19. For this pre-registered systematic review and meta-analysis (PROSPERO ID CRD42021239750) we searched MEDLINE, EMBASE, CINAHL and PsycINFO to 20th February 2021, plus our own curated database. We included peer-reviewed studies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
136
1
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(179 citation statements)
references
References 81 publications
9
136
1
10
Order By: Relevance
“…Likewise, an early in-person follow-up study in Wuhan, China, found sleep abnormalities to be one of the most reported complications amongst 1733 discharged patients 6 months post-disease onset, affecting roughly 26% of their cohort [ 29 ]. Similar findings were reported in studies across Europe, including France and the U.K. where sleep difficulties affected 30.8% and 24% of survivors, respectively, 3–4 months following symptom onset and hospitalization [ 14 , 36 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Likewise, an early in-person follow-up study in Wuhan, China, found sleep abnormalities to be one of the most reported complications amongst 1733 discharged patients 6 months post-disease onset, affecting roughly 26% of their cohort [ 29 ]. Similar findings were reported in studies across Europe, including France and the U.K. where sleep difficulties affected 30.8% and 24% of survivors, respectively, 3–4 months following symptom onset and hospitalization [ 14 , 36 ].…”
Section: Discussionsupporting
confidence: 86%
“…Another recently published systematic review including 51 studies (n = 18,917 patients) also reported persistent problems with sleep disturbance (27%), anxiety (19%), depression PTSD (16%), and cognitive impairment (20%). There was little or no evidence of differences in prevalence based on hospitalization status, disease severity or follow-up duration [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of whether COVID-19 patients were symptomatic or asymptomatic during the acute phase of illness, 10-20% of them will experience Long COVID symptoms within weeks to months after recovery (Huang, Pinto et al 2021, World Health Organization 2022). Other results show that 80% of the recovered COVID- 19 patients suffer from at least one of the Long COVID symptoms, including fatigue, memory impairment, anxiety and depression (Lopez-Leon, Wegman-Ostrosky et al 2021, Badenoch, Rengasamy et al 2022). Interestingly, the prevalence of Long COVID is not affected by hospitalization status, disease severity, or length of follow-up (Davido, Seang et al 2020, Badenoch, Rengasamy et al 2022).…”
Section: Introductionmentioning
confidence: 98%
“…Other results show that 80% of the recovered COVID- 19 patients suffer from at least one of the Long COVID symptoms, including fatigue, memory impairment, anxiety and depression (Lopez-Leon, Wegman-Ostrosky et al 2021, Badenoch, Rengasamy et al 2022). Interestingly, the prevalence of Long COVID is not affected by hospitalization status, disease severity, or length of follow-up (Davido, Seang et al 2020, Badenoch, Rengasamy et al 2022).…”
Section: Introductionmentioning
confidence: 98%
“…There have been heterogenous methods to investigate Long COVID, whether qualitative [26][27][28][29][30] or quantitative 7 , or symptom surveys 31 versus cohort studies 4,32 . Most research still focuses on individual organs [33][34][35][36] . The scale of Long COVID burden necessitates action to develop, evaluate and implement evidence-based investigation, treatment and rehabilitation 37 (e.g., STIMULATE-ICP and other studies 4 ).…”
Section: Discussionmentioning
confidence: 99%